Nilai Karakter Pada Buku Mata Pelajaran Pai Budi Pekerti Berdasarkan Kurikulum Merdeka - Robiatul Adawiyyah Zarkasih; Achmad Marzuki; Adhmad Ma'ruf (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Character education is a joint effort of the school community to create a learning environment that is conducive to the growth and formation of the morals of each individual involved in education. However, in its journey, education has undergone curriculum changes and innovations in order to achieve the goals of National Education as stipulated in Law Number 20 of 2003 concerning the National Education system. This study aims to internalize the character values ​​in the PAI Budi Pekerti book at the SD level for grades 1 and 4. And what about the character values ​​in the PAI Budi Pekerti book for SD grades 1 and 4. This research is a library research (Library Research), by discussing how the Character Values ​​in Islamic Religious Education Subject Books Based on the Independent Curriculum (Content Analysis of Elementary Student Books Grades 1 and 4). Data collection techniques used in research are in the form of literature/library research/library research, namely looking for data about things or variables in the form of notes, books, papers or articles, journals and so on. The data analysis technique used in library research uses the content analysis method. And the validity of the data the researchers found using the triangulation method. The results of this study indicate that this research refers to the Character Profile of Pancasila Students which will later be examined in the book Islamic Religious Education and Characteristics for Elementary School Grades 1 and 4 based on the independent curriculum which consists of six dimensions of Pancasila student profiles, namely: 1) Faithful and devoted to God Almighty, and has noble character, 2) Independent, 3) Mutual cooperation, 4) Global diversity, 5) Critical reasoning, 6) and Creative. Keywords: Character Values, Book of PAI Budi Pekerti, Merdeka Curriculum